Transformative Learning for a New Worldview - Jackson, M. author. aut Link
XV, 216 p.
Keywords: Transformative learning is a process in which we question all the assumptions about the world and ourselves that make up our worldview, visualize alternative assumptions, and then test them in practice. The author describes the process, offering a critique of contemporary assumptions, and suggests alternatives to illustrate the process.